Design and Development of a Web-based System for Ras Fragrance - Ismail, Auni Fawwaz; Wahid, Norfaradilla (Applied Information Technology And Computer Science, 2026)
The local perfume brands in Malaysia are getting recognition with their handcrafted and uniqueness of the products. The finest ingredients are being used carefully to create the scent that reflects the Malaysia’s vibrant landscape and cultural. However, there are many local perfume brands that are still remain unknown including Ras Fragrance. The main objective of this project is to develop a system for Ras Fragrance that capable to help the customers find the suitable scents for them and afterwards perform the online purchasing of the perfume. Another featureas also include user registration, perfume purchasing management, secured payment, fragrance personalization, dashboard management, inventory management and educational content special made for perfume enthusiast. For the development of the project, prototype model which is the best fit for this web-based system. The technologies used in developing this project are PHP language, MySQL and Toyyibpay. This propsed system is fully-completed as it is expected to widen the brand widely in showcasing the product and helping in inventory management. The system also guarantee a smooth quiz perfume experience, a seamless shopping process and real-time synchronization with the inventory perfume updates.